Responses of growth performance, antioxidant function, small intestinal morphology and mRNA expression of jejunal tight junction protein to dietary iron in yellow-feathered broilers - Kaiwen Lei; Hao Wu; Jerry W Spears; Xi Lin; Xi Wang; Xue Bai; Yanling Huang (Journal of Integrative Agriculture, 2024)
This study aimed to investigate the dose-effect of iron on growth performance, antioxidant function, intestinal morphology, and mRNA expression of jejunal tight junction protein in 1- to 21-d-old yellow-feathered broilers. A total of 720 1-d-old yellow-feathered male broilers were allocated to 9 treatments with 8 replicate cages of 10 birds per cage. The dietary treatments were consisted of a basal diet (contained 79.6 mg Fe kg–1) supplemented with 0, 20, 40, 60, 80, 160, 320, 640, and 1,280 mg Fe kg–1 in the form of FeSO4·7H2O. Compared with the birds in the control group, birds supplemented with 20 mg Fe kg–1 had higher average daily gain (ADG) (P<0.0001). Adding 640 and 1,280 mg Fe kg–1 significantly decreased ADG (P<0.0001) and average daily feed intake (ADFI) (P<0.0001) compared with supplementation of 20 mg Fe kg–1. Malondialdehyde (MDA) concentration in plasma and duodenum increased linearly (P<0.0001), but MDA concentration in liver and jejunum increased linearly (P<0.05) or quadratically (P<0.05) with increased dietary Fe concentration. The villus height (VH) in duodenum and jejunum, and the ratio of villus height to crypt depth (V/C) in duodenum decreased linearly (P˂0.05) as dietary Fe increased. As dietary Fe increased, the jejunal relative mRNA abundance of claudin-1 decreased linearly (P=0.001), but the jejunal relative mRNA abundance of zona occludens-1 (ZO-1) and occludin decreased linearly (P˂0.05) or quadratically (P˂0.05). Compared with the supplementation of 20 mg Fe kg–1, the supplementation of 640 mg Fe kg–1 or higher increased (P˂0.05) MDA concentrations in plasma, duodenum, and jejunum, decreased VH in the duodenum and jejunum, and the addition of 1,280 mg Fe kg–1 reduced (P˂0.05) the jejunal tight junction protein (claudin-1, ZO-1, occludin) mRNA abundance. In summary, 640 mg of supplemental Fe kg–1 or greater was associated with decreased growth performance, increased oxidative stress, disrupted intestinal morphology, and reduced mRNA expression of jejunal tight junction protein.